Selective activity of extracts of Margaritaria discoidea and Homalium africanum on Onchocerca ochengi - Nyongbela Kennedy D; Ngemenya Moses N; Abongwa Melanie; Cho-Ngwa Fidelis (BMC, 2010)
Abstract Background The current treatment of onchocerciasis relies on the use of ivermectin which is only microfilaricidal and for which resistant parasite strains of veterinary importance are increasingly being detected. In the search for novel filaricides and alternative medicines, we investigated the selective activity of crude extracts of Margaritaria discoidea and Homalium africanum on Onchocerca ochengi, a model parasite for O. volvulus. These plants are used to treat the disease in North West Cameroon. Methods Sixteen crude extracts were prepared from various parts of M. discoidea and H. africanum using different organic solvents. The filaricidal activities were determined in vitro. Cytotoxicity of the active extracts was assessed on monkey kidney epithelial cells in vitro and the selectivity indices (SI) of the extracts determined. Acute toxicity of the promising extracts was investigated in mice. Results Four out of the 16 extracts showed microfilaricidal activity based on motility reduction, whereas, none showed macrofilaricidal activity based on the MTT/formazan assay. The methylene chloride extract of H. africanum leaves (HLC) recorded the lowest IC50 of 31.25 μg/mL and an IC100 of 62.5 μg/mL. The SI for the active extracts ranged from 0.5 - 2.63. No form of acute toxicity was observed in mice. Phytochemical analysis revealed the presence of anthraquinones, sterols and terpenoids in the promising extracts. Conclusions The non-polar extracts of M. discoidea and H. africanum are potential sources of new microfilaricidal lead compounds, and the results support their use in traditional medicine.